The Impact of Machine Learning on Fraud Detection in Digital Payment - Akinnagbe, Olayiwola Blessing; Akintayo, Taiwo Abdulahi (Darul Yasin Al Sys, 2025)
The rapid adoption of digital payment systems has revolutionized financial transactions, but it has also introduced significant challenges in combating fraud. Traditional rule-based fraud detection methods are increasingly inadequate against sophisticated and evolving fraud schemes. This research explores the transformative impact of machine learning (ML) on fraud detection in digital payments. By leveraging advanced ML techniques such as supervised learning, unsupervised learning, and deep learning, financial institutions and payment platforms can analyze vast amounts of transaction data in real-time, identify complex patterns, and adapt to emerging threats. Case studies from industry leaders like PayPal, Stripe, and Mastercard demonstrate the effectiveness of ML in reducing false positives, improving detection accuracy, and enhancing scalability. However, challenges such as data quality, model interpretability, and adversarial attacks remain critical concerns. This study highlights the benefits, limitations, and future trends of ML in fraud detection, emphasizing its potential to create a more secure and resilient digital payment ecosystem. As fraudsters continue to innovate, the integration of machine learning with emerging technologies like explainable AI (XAI) and blockchain promises to further strengthen fraud prevention efforts, ensuring the safety and trust of digital payment systems worldwide.